Pengaruh Fraud Pentagon dalam Mendeteksi Kecurangan Laporan Keuangan Pada Perusahaan BUMN - Anwar, Mika Alaika; Zakaria, Adam; Musyaffi, Ayatulloh Michael (LPPM Universitas Negeri Jakarta, 2025)
This study aims to experimentally examine the effectiveness of the fraud pentagon in detecting fraudulent financial statements. For the years 2018–2022, state-owned businesses make up the study's population. The sample approach used in this study was purposeful sampling, which produced 125 data points in total. Multiple linear regression analysis was the data analysis method employed in this study, and SPSS Version 26 was used to analyze the data. The results of the study show that only financial targets have a significant impact on the detection of fraudulent financial statements; political connections, frequent changes in the CEO's image, external pressure, insufficient monitoring, and changes in directors or auditors have no effect on the detection of fraudulent financial statements. In elucidating the impact of the fraud pentagon in identifying fake financial statements, this study has bolstered agency theory.